(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
An analysis on the forest of Arden in Shakespeare’sAs You Like It, this essay contrasts the superficial and in-depth views of nature. This piece dives into the imagery, characters, and moral conflicts of Duke Senior and Jaques, ultimately investigating the question of how humans confront challenges. For additional context, listen to the author’s reflection on the piece below.